(untitled) (Advancements in Homeopathic Research, 2022)
“Law of Least” i.e., the quantity of action necessary to effect any change in nature is the least possible, was discovered by the great mathematician Maupertius. Dr. Finche says/said that the decisive movement is always a minimum and infinitesimal i.e., “maxima minimum”. Biochemistry of blood group shows only very minute quantities of salt which are able to maintain a proper equilibrium. Any slightest disturbance towards either more or less upsets the whole system in no time.